Design and Development of Biomimetic Nanovesicles Using a Microfluidic Approach. Issue 15 (7th March 2018) - Molinaro, Roberto; Evangelopoulos, Michael; Hoffman, Jessica R.; Corbo, Claudia; Taraballi, Francesca; Martinez, Jonathan O.; Hartman, Kelly A.; Cosco, Donato; Costa, Giosue'; Romeo, Isabella; Sherman, Michael; Paolino, Donatella; et al.
Abstract: The advancement of nanotechnology toward more sophisticated bioinspired approaches has highlighted the gap between the advantages of biomimetic and biohybrid platforms and the availability of manufacturing processes to scale up their production. Though the advantages of transferring biological features from cells to synthetic nanoparticles for drug delivery purposes have recently been reported, a standardizable, batch‐to‐batch consistent, scalable, and high‐throughput assembly method is required to further develop these platforms. Microfluidics has offered a robust tool for the controlled synthesis of nanoparticles in a versatile and reproducible approach. In this study, the incorporation of membrane proteins within the bilayer of biomimetic nanovesicles (leukosomes) using a microfluidic‐based platform is demonstrated. The physical, pharmaceutical, and biological properties of microfluidic‐formulated leukosomes (called NA‐Leuko) are characterized. NA‐Leuko show extended shelf life and retention of the biological functions of donor cells (i.e., macrophage avoidance and targeting of inflamed vasculature). The NA approach represents a universal, versatile, robust, and scalable tool, which is extensively used for the assembly of lipid nanoparticles and adapted here for the manufacturing of biomimetic nanovesicles. Abstract : The microfluidic platform NanoAssemblr is used to synthesize biomimetic nanovesicles. This platform enables the high‐throughput, reproducible, and scalable production of nanoparticles, without affecting their pharmaceutical and biological properties. The versatility of this approach makes it suitable for good‐manufacturing‐practice‐compliant manufacture of biomimetic nanoparticles.